Selected themes in African development studies : political conflict and stability - Asuelime, Lucky; Francis, Suzanne, 1970- (Advances in African economic, social and political development,, 2014)
Against the background of a long and continuing record of political instability in Africa, this edited collection presents a multi-disciplinary approach to selected issues in African political studies. The contributions explore a range of political and conflict situations, discuss efforts to develop Indigenous conflict resolution mechanisms and consider some of the key political and economic issues facing the continent. The specific country studies illuminate the diversity of the African continent and indicate the ways in which the political and socio-economic contexts of African states bear directly upon the ability of states to solve political and economic challenges. The volume seeks to present and promote novel analytical frameworks, conceptual approaches and empirical accounts of relevance to scholars working on Africa and to practitioners and policy makers in politics, governance and peace initiatives in Africa.